Correlation between visual field index and quality of life in glaucoma patients: a new tool to screen quality of life perception? - Rossi, Gemma Caterina Maria; Milano, Giovanni; De Silvestri, Annalisa; Savini, Lorenzo; Bosi, Chiara; Gambini, Giulia; Rama, Paolo (Frontiers in Medicine, 2023)
Purpose To evaluate the correlation between the visual field index (VFI) and vision-related quality of life (QoL) considering several confounding variables that may have a positive or negative effect. Methods We conducted a cross-sectional, mono-centric study on glaucoma patients. Quality of life was examined with the NEI-VFQ 25 and the Glaucoma Symptom Scale (GSS). The visual field was examined with the Humphrey Field Analyzer. The variables considered were age, gender, comorbidities, years (at diagnosis and duration of the illness), treatment and related active principles, intraocular pressure, and visual acuity. The analysis was performed on both the better and the worse eye. The linear regression univariate analysis and the multivariate analyses were performed. Results In total, 193 patients enrolled in the study. The mean age was 70.8 ± 10.4 years. The mean follow-up period since diagnosis 11.4 ± 9.2 years. Approximately 50% of the patients suffered from primary open angle glaucoma (POAG) and 45% were on monotherapy. The mean VFI was 81.3 ± 26. Regarding QoL, the NEI-VFQ total mean was 80.4 ± 17.8 and the GSS total score was 77.2 ± 21. Regarding NEI-VFQ 25, the single linear regression analysis found the following relations: age at time of visit (r = −0.30, p = 0.016), years of illness (r = −0.32, p = 0.020), the minimum and maximal visual acuity (r = 2.04 and r = 3.96, p < 0.001), the IOP min (r = 1.13, p = 0.002) and max (r = −0.52, p = 0.017), and the number of previous surgeries (r = −3.94, p < 0.001). The multivariate analysis found the following relations: gender (r = 5.13, p = 0.019), visual acuity max (r = 3.16, p < 0.001), and previous surgeries (r = −1.80, p = 0.032). Regarding GSS, the single linear regression analysis found relations with visual acuity (r = 2.37, p < 0.001), VFI (r = 0.41, p < 0.001), previous surgeries in the eye considered (r = −7.27, p < 0.001), and number of instillations (r = −3.67, p = 0.031). Data confirmed that a higher VFI has a positive impact on the score of both the NEI-VFQ 25 (r = 0.22, p = < 0.001) and the GSS questionnaire (r = 0.36, p < 0.001). Conclusions The study demonstrated a correlation between the VFI and QoL of patients and their visual and non-visual ocular symptoms and function both in the worst and in the better eye, even when accounting for several clinical and demographic confounding variables. Our data support that the visual field index is an important metric instrument in the follow up of patients with glaucoma.